24.4k views
5 votes
Evaluate the expression using the values in the left column to complete the table

Evaluate the expression using the values in the left column to complete the table-example-1
User Greenhoe
by
5.0k points

1 Answer

7 votes

Answer/Step-by-step explanation:

A.
4b + 3b

Using b = 2


4(2) + 3(2) = 8 + 6 = 14

Using b = 4


4(4) + 3(4) = 16 + 12 = 28

Using b = 6


4(6) + 3(6) = 24 + 18 = 42

Using b = 8


4(8) + 3(8) = 32 + 24 = 56

Using b = 10


4(10) + 3(10) = 40 + 30 = 70

Using b = 2


4(12) + 3(12) = 48 + 36 = 84

B.
3(x - 2)

Using x = 3


3(3 - 2) = 3(1) = 3

Using x = 5


3(5 - 2) = 3(3) = 9

Using x = 7


3(7 - 2) = 3(5) = 15

Using x = 9


3(9 - 2) = 3(7) = 21

Using x = 11


3(11 - 2) = 3(9) = 27

Using x = 13


3(13 - 2) = 3(11) = 33

C.
5(4a - 1)

Using a = 2


5(4(2) - 1) = 5(8 - 1) = 5(7) = 35

Using a = 3


5(4(3) - 1) = 5(12 - 1) = 5(11) = 55

Using a = 4


5(4(4) - 1) = 5(16 - 1) = 5(15) = 75

Using a = 5


5(4(5) - 1) = 5(20 - 1) = 5(19) = 95

Using a = 6


5(4(6) - 1) = 5(24 - 1) = 5(23) = 115

Using a = 7


5(4(7) - 1) = 5(28 - 1) = 5(27) = 135

D.
6y - 2y + 4

Using y = 2


6(2) - 2(2) + 4 = 12 - 4 + 4 = 12

Using y = 3


6(3) - 2(3) + 4 = 18 - 6 + 4 = 18 - 2 = 16

Using y = 5


6(5) - 2(5) + 4 = 30 - 10 + 4 = 30 - 6 = 24

Using y = 10


6(10) - 2(10) + 4 = 60 - 20 + 4 = 60 - 16 = 44

Using y = 8


6(8) - 2(8) + 4 = 48 - 16 + 4 = 48 - 12 = 36

Using y = 6


6(6) - 2(6) + 4 = 36 - 12 + 4 = 36 - 8 = 28

User Houston
by
5.3k points